Wąż i jego symbolika w Biblii - Lemański, Janusz Adam (Verbum Vitae, 2017)
A serpent or viper is one of the most popular symbols within many cultures word-wide. In the Ancient Near East it had positive as well as negative connotations, but in the Bible the latter predominate. There, the serpent typically represents chaos, magic, a state of threat, death, or deceit. Nevertheless, among the numerous biblical metaphors and comparisons employing the image of the serpent or viper, there are some which present a positive image. In the older strata of biblical texts, especially those taken from the Book of Exodus (Chapters 4 and 7) or the Book of Numbers (Chapter 21), we find positive references in which a serpent represents JHWH and his healing power.